1998
DOI: 10.1200/jco.1998.16.1.121
|View full text |Cite
|
Sign up to set email alerts
|

p53 protein accumulation predicts poor response to tamoxifen therapy of patients with recurrent breast cancer.

Abstract: Measurement of primary tumor p53 levels may be effective in predicting response to tamoxifen therapy in recurrent breast disease. However, more confirming studies on the association between p53 protein accumulation and response to antiestrogen therapy are needed before tumor p53 levels can be used in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 25 publications
2
26
0
2
Order By: Relevance
“…However, it has also been concluded that p53 mutation or accumulation predicts poor response to tamoxifen (14,48). The results in the present study demonstrated that the patients with both normal and altered p53 status appear to have a good response to tamoxifen.…”
Section: Discussionsupporting
confidence: 64%
“…However, it has also been concluded that p53 mutation or accumulation predicts poor response to tamoxifen (14,48). The results in the present study demonstrated that the patients with both normal and altered p53 status appear to have a good response to tamoxifen.…”
Section: Discussionsupporting
confidence: 64%
“…In 1995, Foekens et al [37] first reported that high levels of uPA predicted resistance to tamoxifen in patients with advanced breast cancer. The association between high expression of uPA and lack of response to the antiestrogen appeared to be independent of ER and PR status [37,38]. However, the predictive ability of the protease was found only in a subset of patients, i.e., those with intermediate levels of steroid receptors (>10 fmol/mg protein for both receptors with at least one being not more than 75 fmol/mg protein) [37].…”
Section: Breast Cancermentioning
confidence: 89%
“…Here, p53 mutations are a strong predictor of treatment failure, relapse and death [21,72]. For example, p53 mutations are associated with resistance to tamoxifen [22,73], radiotherapy [24,74] and doxorubicin [23]. While theses correlations are provocative, it should be noted that some studies find no correlation [75,76].…”
Section: P53 Mutations and Drug Resistancementioning
confidence: 89%